The effect of job insecurity on labour supply - Jara Tamayo, Holguer Xavier (Colchester, 2013)
"The aim of this paper is to analyse the efect of job insecurity on labour supply. We propose an extension of traditional discrete choice models of labour supply in order to allow for the introduction of non-pecuniary job attributes in the analysis. In our extended model, the choice alternatives are characterised by bundles of income, hours of work and job insecurity. We compare the predictive power and labour supply elasticities obtained with our model to those of a traditional model where only income and discrete hours choices characterise a job. The results show that once job insecurity is included in the discrete choice alternatives, the predictive power of the model improves signifi?cantly. Labour supply elasticities are significantly higher than those obtained with a traditional model and increase with the level of job insecurity. Finally, a decrease of job insecurity at work has a positive and significant effect on participation. Policies aimed at improving working conditions could, in this sense, be useful to create incentives in labour market."